High-performance PtCux@Pt core-shell nanoparticles decorated with nanoporous Pt surfaces for oxygen reduction reaction - Jung, Namgee; Sohn, Yeongun; Park, Jin Hoo; Nahm, Kee Suk; Kim, Pil; Yoo, Sung Jong (ELSEVIER SCIENCE BV, 2016)
PtCux@Pt/C (x=3, 5, and 7) core-shell catalysts with nanoporous Pt surfaces were synthesized via the galvanic replacement reaction. The surface morphology and elemental compositions of the PtCux@Pt/C catalysts were significantly influenced by the initial ratio of Cu to Pt in the PtCux nanoparticle substrates, and porous surfaces on the PtCux@Pt nanoparticles could be produced when the Cu to Pt ratios in the PtCux nanoparticle substrates were greater than 5. In addition, the nanoporous PtCux@Pt nanoparticles showed different electronic structures depending on the surface to bulk compositions. Therefore, the oxygen reduction reaction (ORR) activities of the PtCux@Pt/C catalysts were significantly influenced by the surface morphologies and atomic ratios of Cu to Pt near the surface of the nanoparticles. Among the PtCux@Pt/C catalysts synthesized, PtCu7@Pt/C catalyst with a nanoporous Pt surface exhibited superior ORR activity and durability compared to a commercially available Pt/C JM catalyst. The d-band downshift of the PtCu7@Pt/C catalyst by the formation of highly porous Pt layers on the Cu-enriched subsurface layer resulted in the enhancement of the catalytic activity and durability for the ORR. High durability of the PtCu7@Pt/C catalyst was attributed mainly to the increase in the dissolution potential of the Pt surface layers on the Cu-enriched subsurface layer. The Cu dissolution from the subsurface regions of the nanoparticles was also considerably retarded, owing to the surface protection offered by stable Pt shell layers. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: GALVANIC REPLACEMENT REACTION; FUEL-CELL; BIMETALLIC NANOPARTICLES; ENHANCED ACTIVITY; SKIN SURFACES; ELECTROCATALYSTS; STABILITY; NANOCATALYSTS; MONOLAYER; CATALYSIS